First-line treatment with zolbetuximab plus CAPOX for ClDN18.2-positive gastric or gastroesophageal junction adenocarcinoma: a cost-effectiveness analysis - Jianying Lei; Jiahao Zhang; Caicong You; Wu Fu; Maobai Liu; Na Li (Therapeutic Advances in Gastroenterology)
Background: Patients with HER2-negative locally advanced or unresectable metastatic gastric cancer and gastroesophageal junction (G/GEJ) adenocarcinoma have limited first-line treatment options and a poor prognosis. The GLOW clinical trial showed that zolbetuximab plus capecitabine plus oxaliplatin (CAPOX) significantly prolonged these patients’ overall survival (OS) and progression-free survival (PFS). Objectives: This study evaluated the cost-effectiveness of zolbetuximab plus CAPOX as a first-line treatment for HER2-negative locally advanced or unresectable metastatic G/GEJ adenocarcinoma in the United States and China. Design: The cost-effective analysis. Methods: Based on the GLOW clinical trial data (NCT03653507), we constructed a 10-year Markov model to assess the cost-effectiveness of the zolbetuximab or placebo plus CAPOX treatment regimen. Only direct medical costs were considered. The primary outcomes of the model were quality-adjusted life-years (QALYs) and incremental cost-effectiveness ratios (ICERs). One-way and probabilistic sensitivity analyses were employed to assess the robustness of the model. Results: In the United States, zolbetuximab plus CAPOX added 0.24 QALYs and resulted in an incremental cost of $196,791.11 compared with placebo plus CAPOX, which had an ICER of $821,515.65 per QALY gained. For China, the zolbetuximab group gained 0.23 QALYs at an incremental cost of $62,822.69, resulting in an ICER of $273,568.01/QALY. One-way sensitivity analysis revealed that the results were most sensitive to the price of zolbetuximab. Zolbetuximab plus CAPOX had 0% cost-effectiveness at the willingness-to-pay thresholds of $150,000/QALY in the United States and $38,188/QALY in China. Conclusion: Zolbetuximab plus CAPOX may be a cost-effective option for patients with locally advanced, unresectable, or metastatic G/GEJ adenocarcinoma when the price of zolbetuximab reduced by 83.37% ($367.7/100 mg) in the United States and 82.25% ($110.8/100 mg) in China.